Governing Through Accountability: Gender Equality and the United Nations - Cole, Sally; Phillips, Lynne (Atlantis, 2008)
This article investigates the audit culture of UNIFEM, an international organization dedicated to bringing about global gender equality. UNIFEM's strategic plans, regional activities, and one fund-raising activity are analyzed to illustrate how pressures to "manage for results" combine with the UN's promotion of a transnational, modernist ethos to shape gender equity policy and, ultimately, what we know about women's lives.